The evaluation of liquid disinfectants to reduce Salmonella contamination on animal food manufacturing surfaces - Muckey, M. B.; Huss, A. R.; Jones, Cassandra K. (My University, 2016)
Recent research had demonstrated that Salmonella and Porcine Epidemic Diarrhea Virus have been isolated from feed, ingredients, and feed manufacturing equipment surfaces. However, there is limited data regarding the sanitation of animal food manufacturing surfaces. The objective of this experiment was to evaluate the effects of liquid chemical treatments to reduce Salmonella contamination of metal surfaces. Metal coupons (103cm2, stainless steel 316; Built-so-Well, Manhattan, KS) were placed in sterile Petri dish, and inoculated with 1 mL of Salmonella Typhimurium Coupons were incubated overnight at 35°C, then subjected to treatments for 15 min: 1) no inoculation or sanitation treatment (positive control), 2) inoculated with no sanitation treatment (negative control), 3) inoculated and treated with a liquid alcohol-based commercial equipment sanitizer (DrySan Duo, Ecolab, St. Paul, MN), and 4) inoculated and treated with a liquid formaldehyde-based commercial product (SalCURB; Kemin Inc., Des Moines, IA). Immediately following treatment, excess material was removed by tapping. The coupon was then swabbed and the swab vortexed in neutralizing broth (EMD Chemicals, Darmstadt, Germany) before dilution. Samples were then serial diluted (10?1 to 10?6) and spread to Trypticase Soy Agar plates. Plates were incubated at 35°C for 24 h, and then enumerated. The quantity of Salmonella colony forming units (CFU) are depicted as CFU/cm2. Data were analyzed using the GLIMMIX procedure of SAS as a completely randomized design with 3 replicates per treatment. As expected, treatment affected (P < 0.0001) residual Salmonella concentration, and there was no growth on the positive control treatment. The liquid formaldehyde-based commercial product was highly effective, resulting in no detectable growth (P < 0.05). Treating metal surfaces with the liquid alcohol-based commercial equipment sanitizer reduced (P < 0.05) Salmonella concentrations by 2 logs compared to the negative control. Liquid sanitizer treatment of metal surfaces led to a reduction in Salmonella, and can be effective steps in bacterial contamination in feed and animal food manufacturing. However, liquid sanitizers have drawbacks because they may be corrosive and most feed manufacturing equipment is not designed as clean-in-place to withstand liquid sanitation. More research is needed to evaluate dry sanitation methods that are able to break biofilms and sanitize animal food manufacturing surfaces.
Citation: Muckey, M. B., Huss, A. R., & Jones, C. K. (2016). The evaluation of liquid disinfectants to reduce Salmonella contamination on animal food manufacturing surfaces. Journal of Animal Science, 94, 79-79. doi:10.2527/msasas2016-168
Keywords: Feed; Sanitation; Salmonella; Agriculture